Intelligence and Global Transportation Supply Chain Management: The Case of Oil and Gas Supply in the Gulf of Guinea - Nte, Ngboawaji Daniel (Department of Ocean Engineering, Faculty of Engineering, Hasanuddin University, 2026)
The Gulf of Guinea (GoG) is a critical artery for global oil and gas distribution, yet its supply chain is plagued by a complex risk ecosystem. This study investigates the imperative of intelligence management in mitigating these risks. Employing a mixed-methods approach, it integrates quantitative data from the International Maritime Bureau (IMB) and MDAT-GoG (2020-2024) with qualitative insights from focused group interviews with 12 security and industry experts. The findings reveal an evolution in maritime criminality towards armed robbery and theft, persistent infrastructure deficits that act as risk multipliers, and a critical